Epidemiology and outcome of non viral keratitis - Talukder, AK; Halder, SK; Sultana, Z; Bhuiyan, SI (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jul;20(3):356-361 The abstract of this article is available on the PubMed website